Marketing Mix Jasa Pendidikan Sebagai Strategi Peningkatan Kuantitas Peserta Didik di MA Muhammadiyah 5 Sidoharjo - Dian Pratiwi; Awalul Inayati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
Marketing mix as a marketing tool must be considered and managed properly so that marketing in educational institutions runs successfully. This study aims to analyze (1) the application of marketing education services at MA Muhammadiyah 5 Sidoharjo; (2) the steps of marketing mix education services as a strategy to increase the quantity of students at MA Muhammadiyah 5 Sidoharjo; and (3) increasing the quantity of students at MA Muhammadiyah 5 Sidoharjo. The research was designed using qualitative research methods that emphasize understanding of problems in social life based on real conditions or natural settings that are holistic, complex and detailed. Type of case study research. Data collection is done through in-depth interview procedures, observation, and documentation. Informants or sources in this study came from principals, educators, education personnel, students, and student guardians. Then the research data were analyzed using the Miles and Huberman analysis model, namely data condensation, data presentation, and conclusion drawing. Based on the results of data analysis, it was found that (1) the application of marketing of educational services that should be considered and schools should be able to make appropriate marketing strategies more specifically schools in managing marketing of their educational services must do analysis, organization, planning, control, (2) the steps of the marketing mix strategy applied at MA Muhammadiyah 5 Sidoharjo some of which are no payment for building fees and making payment options, located in a strategic place then they use social media as a tool for disseminating information in marketing activities. (3) there was an increase in the number of students at MA Muhammadiyah 5 Sidoharjo after experiencing a very drastic decline in 2019 where the incoming students were less than 10 students, and with a new strategy by carrying out the theme of natural schools in 2020 they experienced an increase in the number of students, namely students who entered 14 students.